2010
DOI: 10.1149/1.3484640
|View full text |Cite
|
Sign up to set email alerts
|

3D Imaging of Polymer Electrolyte Fuel Cell Electrodes

Abstract: The degradation of Polymer Electrolyte Fuel Cell (PEFC) electrodes was examined by electrochemical and 3D imaging methods. A potential cycling test was conducted with a commercial catalyst coated membrane (CCM) where the cathode side of the cell was subjected to a potential square wave of 0.6V and open circuit voltage. After 24000 cycles, the PEFC performance remains nearly unchanged except for minor current losses in the low current regime. According to hydrogen under potential desorption measurements the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…32 Focused ion beam (FIB) milling combined with SEM can provide high-resolution 3D morphology of the catalyst layer. 26,33 However, FIB-SEM faces its own set of challenges. It is a destructive technique, and differential milling rates for different materials can be intrusive.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Focused ion beam (FIB) milling combined with SEM can provide high-resolution 3D morphology of the catalyst layer. 26,33 However, FIB-SEM faces its own set of challenges. It is a destructive technique, and differential milling rates for different materials can be intrusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…35 As an alternative to electron microscopy, microscale and nanoscale resolution X-ray computed tomography (CT) can be used to image fuel cell components. 26,36 Advances in diffraction-based X-ray optics using monocapillary condensers and Fresenel zone plate objectives has led to X-ray CT imaging at resolutions of 50 nm and better. Epting et al 36 previously demonstrated that nano-CT can be used to image the pore and solid structure of fuel cell catalyst layers, where the solid was the dense regions of Pt/C catalyst and Nafion ionomer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the morphologic structures and transport processes of CL, some ex-situ techniques have been explored, including mercury intrusion porosimetry 113 , focused ion beam scanning electron microscope (FIB-SEM) or scanning transmission electron microscope (STEM) 114 . Although high-resolution 3D morphology of CL can be obtained through FIB-SEM and STEM, there are some challenges for these methods, for instance, FIB-SEM itself is a destructive technique.…”
Section: Pgm-free Electrocatalysts and Layers As A Promising Alternativementioning
confidence: 99%